THE METAL CLIPS AS BREAST CANCER MARKERS IN ASSESSMENT OF RESPONSE AFTER NEOADJUVANT CHEMOTHERAPY - Gambarova, G.H.; Аскерова, Х.Є.; Aghamaliyeva, A.J.; Panahova, M.S.; Агабейлі, Л.З.; Qorchiyeva, G.S. (World of Medicine and Biology, 2024)
The purpose of the study was to investigate the features of using surgical clips as tumor localization markers in patients with breast cancer and influence responses after neoadjuvant chemotherapy. 14 patients (16 lesions) underwent preoperative ultrasonography-guided surgical clip insertion before neoadjuvant chemotherapy. Within the 8–10-day period before surgery follow-up mammography, ultrasonography and magnetic resonance imaging were performed to evaluate treatment response after neoadjuvant chemotherapy. 10 lesions underwent breast conservative surgery, the rest – 6 lesions were treated with modified radical mastectomy. There was no difficulty in the pathological evaluation of a specimen due to inserted surgical clips. The time interval from clip insertion to mammography after procedure and surgery was 38.1±12.4 days and 115.7±28.4 days, respectively. The mean number of inserted clips was 2.1±0.8. Our results have shown that surgical clips are helpful in visualization of tumors and their localization by various imaging methods, well tolerated and safe for the patient, do not interfere with treatment response after neoadjuvant chemotherapy.
Keywords: breast malignancy; breast conservative surgery; pathologic complete remission; radiodense marker